NEGOSIASI TRI DHARMA PERGURUAN TINGGI IBU AKADEMISI INDONESIA - fariza yuniar rakhmawati (Universitas Teuku Umar, 2026)
This study examines how academic mothers in Indonesia make sense of and negotiate academic workload through the lens of Symbolic Interactionism (IS). The Tri Dharma Perguruan Tinggi are treated as institutional symbols that orient action and frame the legitimacy of work. The study employs a phenomenological approach with interviews of 14 academic mothers. Findings indicate that teaching is constructed as a primary professional identity; research is deprioritized due to constraints in facilities, funding, time, and administrative demands, while output labels (accreditation/Scopus) operate as symbols of legitimacy that shape action. Common strategies include collaboration and the use of student research assistants, with grants and networks reinforcing claims to a researcher identity. Community service frequently conflicts with family time because it occurs outside regular working hours. Administrative tasks emerge as the heaviest burden, eroding capacity for other roles. Across these domains, negotiated meaning and order are continually produced through interactions with leaders, colleagues, students, and family.